China’s SO 2 emission reductions enhance atmospheric ozone–driven sulfate aerosol production in East Asia - Yu-Chi Lin; Yan Zhao; Yan-Lin Zhang; Yihang Hong; Shohei Hattori; Syuichi Itahashi; Mei-Yi Fan; Feng Xie; Zhu-Yu Zhao; Mingyuan Yu; Fang Cao; Rongshuang Xu; et al. (Proceedings of the National Academy of Sciences, 2025)
Reduction of China’s SO 2 emissions has been found to nonlinearly decrease the atmospheric sulfate (SO 4 2− ) aerosol concentrations in East Asia. Compared to Europe and North America, the lower effectiveness of SO 4 2− reduction in East Asia suggested much effects of “acidity-sensitive” feedback mechanisms in this high anthropogenic emission region, which have not been yet examined. In this work, we investigated these feedback mechanisms in East Asia through long-term measurements of the mass-independent oxygen-17 anomaly (Δ 17 O) in sulfate aerosols, machine learning and Community Multiscale Air Quality (CMAQ) model. As China’s emissions reduced, the atmospheric acidity decreased, enhancing the ozone-driven oxidation of S(IV) and production efficiency of sulfate formation. This explained the weaker declining SO 4 2− concentrations than SO 2 emissions. By the evidence from observed Δ 17 O in non-sea-salt sulfate (Δ 17 O-nss-SO 4 2− ) and CMAQ simulations, the highly enhanced contributions of S(IV)+O 3 to sulfate driven by reduced SO 2 emissions explained the low effectiveness of SO 4 2− reduction in East Asia. Additionally, the decreases of acidity by substantial NH 3 emissions are projected to continue until 2050, limiting SO 4 2− reduction effectiveness. Thus, we highlighted that global control of both SO 2 and NH 3 emissions are needed to efficiently mitigate the sulfate-related climate and pollution, especially in high NH 3 emission region, such as East Asia.